Evaluation of Withania somnifera based supplement for immunomodulatory and antiviral properties against viral infection - Dileep Kumar Verma; Abdul Hasan; Manickavasagam Rengaraju; Shree Devi; Geetika Sharma; Vimal Narayanan; Sathiyarajeswaran Parameswaran; Thirumal Kumar D; Kanakavalli Kadarkarai; Sujatha Sunil (Journal of Ayurveda and Integrative Medicine)
Background: Viral mediated diseases are continuously posing potent threat to human health. Nutraceuticals are being employed as novel therapeutics during viral outbreaks. MAM granules consist of Curcuma longa, Withania somnifera, and Piper nigrum, is one such patented Siddha nutraceutical supplement that has been proposed to be a therapeutic agent against viral diseases. Objective: We characterised MAM for their phytochemical and physicochemical properties and evaluated its cytotoxicity via in vivo acute toxicity studies using Wistar rats and by cell-based MTT assays. Materials and Methods: The antiviral properties of the aqueous extract of MAM were investigated against SARS-CoV-2 and chikungunya virus (CHIKV). Further, using ABTS radical scavenging, SOD enzymatic assays and measurement of intracellular ROS, we investigated the antioxidant potential of MAM extract and its ingredients in RAW264.7 cells. Additionally, production of inflammatory mediators was evaluated via NO release, PGE2 production and release of pro-inflammatory cytokines (IL-1β and TNFα). Results: The MAM granules and aqueous extracts demonstrated no significant toxicity and demonstrated potent antiviral activity during co-incubation assay with SARS-CoV-2 and CHIKV. Moreover, we observed potent antioxidant and anti-inflammatory activity of MAM extract in a dose dependent manner. Further investigations on the individual ingredients with respect to their antioxidant and anti-inflammatory activities showed that all ingredients contributed synergistically and Withania somnifera showed most potent anti-oxidant activity. Conclusion: The overall in vitro, and in vivo analysis demonstrated that MAM granules were non-toxic and possessed potent antiviral activity. Additionally, observed significant anti-oxidant and anti-inflammatory properties of MAM suggested the modulation of innate immune response in the host validating its use as an effective nutraceutical during viral outbreaks.